Is Bitcoin a Good Investment Asset? - Apolónia, João (2022)
This paper aims to analyze the consequences of adding Bitcoin to an investment portfolio. The main methodology used is the Mean-Variance model combined with the Monte Carlo Simulation. Results show that Bitcoin can improve the Sharpe Ratio of an already diversified portfolio, however the inclusion of Bitcoin has to be done in proportions averaging 3.83 percent of the portfolio’s weight. This paper also found that Bitcoin does not seem to behave as a safe haven/hedge asset during the Covid-19 pandemic.